Evaluation of Poisoning Cases in the Poisoning Consultation Center and Forensic Medicine Institute within Baghdad area - Faris H.Maedie; Hasan Alhaddad; Saad A. Hussain (College of Pharmacy University of Baghdad, 2017)
Social factors may affect the available sources of toxic substances and causes of poisoning, and these factors may change over time. Additionally, understanding the characteristics of poisoning cases is important for treating such patients. Therefore, the present study investigated the characteristics of poisoning cases in Baghdad Poisoning Consultation Center (PCC) and Forensic Medicine Institute (FMI). Data on all poisoning cases reported in PCC and FMI during 2013 were retrospectively obtained from medical records. Total of 1131 reports of poisoning cases (1082 from PCC and 49 from FMI) were analyzed according to age, sex, geographical distribution and causes of poisoning according to the type and class of poisoning agent. The results showed that most of the poisoning case are from urban area, and the incidence in male is greater than that in females. In both centers, the higher percent of poisoning occurred within the age range 11-20 years. Regarding the type of poisons, zinc sulphide and carbon monoxide represent the cause of poisoning reported in MFI, while metals (mostly copper) and drugs (mostly CNS depressants) represent the major causes of toxicity reported in PCC. In conclusion, among the elements that are common between the two centers are the age distribution of the cases. Rodenticides and metals represent the major causes of poisoning cases reported in Baghdad during 2013. The study results suggest that it is necessary to continuously collect data of patients admitted to emergency departments with toxic poisoning at multiple centers. Keywords: Poisoning, Consultation center, Forensic medicine.